Soluble neuropilin-1 in gingival crevicular fluid is associated with rheumatoid arthritis: An exploratory case-control study - Diego Prieto; Camila González; Laura Weber; Ornella Realini; Karina Pino-Lagos; Maria José Bendek; Ignacio Retamal; Víctor Beltrán; Juan Pablo Riedemann; Francisco Espinoza; Alejandra Chaparro (Journal of Oral Biology and Craniofacial Research)
Background: To explore the soluble Neuropilin-1 (sNRP-1) concentrations in gingival crevicular fluid (GCF) and the periodontal clinical status of patients with Rheumatoid Arthritis (RA). Materials and methods: We conducted an exploratory study with 40 study participants, 20 with RA, and 20 healthy controls. Clinical and periodontal data were recorded, and GCF samples were obtained. sNRP-1 levels in GCF were determined by ELISA assay. Descriptive statistics, Mann–Whitney U test, Unpaired t-test, logistic regression model, and Area Under Receiver Operating Characteristic Curve (AUC-ROC) were made to explore the diagnostic performance accuracy. Results: RA patients had significantly higher levels of sNRP-1 in GCF (p ​= ​0.0447). The median levels of GCF-sNRP-1 were 208.85 ​pg/μl (IQR 131.03) in the RA group compared to 81.46 ​pg/μl (IQR 163.73) in the control group. We observed an association between the GCF-sNRP-1 concentrations and the RA diagnosis (OR:1.009; CI 1.00–1.001; p ​= ​0.047). The diagnosis of chronic periodontitis was also associated with RA (OR: 6.9; CI 1.52–31.37; p ​= ​0.012). Moreover, the AUC-ROC of GCF-sNRP-1 concentrations combined with periodontal clinical parameters such as periodontal probing depth and periodontal inflamed surface area was 0.80. Conclusion: This exploratory case-control study shows that RA patients had significantly higher levels of sNRP-1 in GCF. New longitudinal studies are necessary to evaluate the role of NRP-1 in periodontal tissues and consider it an oral biomarker with clinical value in RA.